Investigating multi-directional inhomogeneous granular suspensions - De Klerk, David (Department of Physics, 2020)
Granular flows in rotating drums find many applications in industry, even though the dynamics of their granular media is not fully understood. Several models of granular flow and granular suspensions (where a viscous fluid is present in the voids between the granular particles) have been proposed in the last decade and a half. These models are unified in the way that dimensional analysis is employed to describe bulk properties of the flow in terms of a number of dimensionless parameters. However, applicability to rotating drums has not been demonstrated for many of these models. Furthermore, most studies rely on numerical simulations or experiments of slowly rotating drums that are not easily identified with industrial applications that operate in higher Froude regimes. This thesis presents a series of Positron Emission Particle Tracking (PEPT) experiments and Discrete Element Method (DEM) simulations of rotating drums with a viscous fluid. The three aims of the thesis are, to investigate the use of the Ergodic hypothesis when analysing PEPT data, to test the use of the lubrication approximation in the DEM simulations and to compare results from rotating drums to the latest models of granular rheology and granular suspensions. Two sets of PEPT experiments were carried out with a drum (radius R = 230 mm and length L = 200 mm) which was forced to rotate around its axis. The first series of experiments, used to investigate the use of the ergodic hypothesis, used a fixed rotation rate (ω = 0.6ωc = 0.6 p g/R) and three different particle sizes (5 mm, 8 mm and 10 mm). A radio labelled tracer particle’s location was recorded for 10 h for each of the three particle sizes. The second series of experiments, intended to test rheology models of dense suspensions and the use of the lubrication approximation in DEM, used 10 mm diameter glass spheres and glycerol/water mixtures in a drum. The second configuration was simulated with DEM using the Hertz-Mindlen contact model for particle-particle interactions. The effect of a viscous force between particles in close proximity to each other was captured by a lubrication approximation. Particle level data from experiments and simulations are transformed to smooth fields by a coarsegraining method which is described in detail. The ergodic assumption (which states that time averages of the PEPT tracer is equivalent to the ensemble average and central to analysing PEPT data) is evaluated using the first series of experiments. It was found that the average velocity can be established after 15 min tracking time, however the solids fraction still shows under sampled regions after tracking for 3 h. Several techniques were used to investigate this, including as Poincaré maps and the global mixing index. A variation on the averaging technique is shown to account for under sampled regions in the solids fraction.